Pemberdayaan Budaya Visual Erison J. Kambari dalam Ranah Pelestarian Budaya Lokal Sumatera Barat - Susanti, Indah (Rekam, 2024)
This article reveals the sides of photography  by local photographers. The method used is to analyze the work of Erison J Kamari and the appreciation of the audience for his photographs. The method used in this research is qualitative. The result of this research is how to promote and introduce the local potentials of West Sumatran culture by Erison through his visual records. The actions of this photographer from Kurai provide realization in professional art creation management. Capturing moments that cannot be separated from patience, basic understanding of photography techniques, selection of ideas, writing captions and being able to help promote the tourism sector. Erison's gait was able to invite young photographers to care about the culture of West Sumatra, one of which was through the Jawi race. The implication of this research is that it has a positive impact on the tourism sector and the economy.Keywords: Erison J. Kambari, Visual culture, Photographer and West Sumatra. This article reveals the sides of photography  by local photographers. The method used is to analyze the work of Erison J Kamari and the appreciation of the audience for his photographs. The method used in this research is qualitative. The result of this research is how to promote and introduce the local potentials of West Sumatran culture by Erison through his visual records. The actions of this photographer from Kurai provide realization in professional art creation management. Capturing moments that cannot be separated from patience, basic understanding of photography techniques, selection of ideas, writing captions and being able to help promote the tourism sector. Erison's gait was able to invite young photographers to care about the culture of West Sumatra, one of which was through the Jawi race. The implication of this research is that it has a positive impact on the tourism sector and the economy.Keywords: Erison J. Kambari, Visual culture, Photographer and West Sumatra.